Practical methods for optimal control and estimation using nonlinear programming - Betts, John T., 1943- (Society for Industrial and Applied Mathematics (SIAM, 3600 Market Street, Floor 6, Philadelphia, PA 19104), 2010)
The book describes how sparse optimization methods can be combined with discretization techniques for differential-algebraic equations and used to solve optimal control and estimation problems. The interaction between optimization and integration is emphasized throughout the book.
Description based on title page of print version.
Keywords: Control theory.; Mathematical optimization.; Nonlinear programming.; elektronické knihy; electronic books